Estudo cinético do lixiviado de aterro sanitário tratado por meio do processo de eletrocoagulação - Theodoro, Joseane Debora Peruço (2018)
The present paper aimed to analyze the kinetic behavior of the leachate from a landfill through the electrocoagulation process. It was determined the kinetic parameters of the treatments to the apparent color and turbidity. The obtained results to the reactions of zero order, first and second order by the Integral Method. It was performed three tests, being test one (1) in acid medium (pH=3.58), the test two (2) in neutral medium (pH=7.62), and the test three (3) in basic medium (pH=9.93). For the removal of the apparent color parameter the best results were obtained at pH = 7.62, zero order kinetics, R2 = 0.8094 and reaction rate K = 26.137uHmin-1 for the first order study R2 = 0.8752 and K = 0.0211 min-1 and second order kinetics R² = 0.8823 and K = - 2.00E-05 uH-1.min-1. The turbidity parameter presented significant kinetic behavior only for the first order reaction and in basic medium (pH = 9.93), with R2 = 0.8752 and K = 0.0029 min-1.